Evaluation of the physicochemical and bacteriological quality of groundwater in the Nihit rural commune of the Moroccan Anti-Atlas - Abdallah Assouani; Abdelkader Dabagh; Mhamed Abali; Guellaa Mahmoudy; Mohamed EL-Habacha; Mohamed Chiban; Naima Alahiane; Fatiha Fdil; Fouad Sinan; Mohamed Zerbet (Desalination and Water Treatment)
Our study evaluated the physico-chemical and bacteriological quality of water wells and boreholes in the rural commune of Nihit in the Moroccan Anti Atlas. In this study, we assessed the physico-chemical qualities of the water such as pH, temperature, conductivity, turbidity, nitrate, nitrite, sulfate, mineral elements, and heavy metals. We also studied the bacteriological quality of the water in terms of microbial germs represented by Total Coliforms, Fecal Coliforms, Escherichia coli (E. coli), Intestinal Enterococci, and sulfito-reducing Clostridium.Apart from two points located upstream of the Douars, nitrate concentrations range from 60 to 290 mg.L-1, well above the permissible value according to the World Health Organization (50 mg.L-1). At some points, values reach concentrations of 4.1.103 CFU/100 mL, 1.9.102 CFU/100 mL, 60 CFU/100 mL, 1.8.103 CFU/100 mL, and 90 CFU/100 mL, respectively for total coliforms, fecal coliforms, Escherichia, intestinal enterococci and sulfito-reducing Clostridium. The presence of Total Coliforms, Fecal Coliforms, and E. coli in the water tested is an indicator of contamination by human or animal fecal matter, which may come from conventional septic tanks, untreated wastewater discharges, animal manure leaching, or runoff. On the other hand, the values of the other physicochemical parameters tested remain compliant with potable water standards.